DENSITY OF BUILDINGS IN GROGOL DISTRICT SUKOHARJO DISTRICT 2018 - Deni Anggono; Agus Sudargono; Muh. Husyain Rifai (Universitas Veteran Bangun Nusantara, 2021)
The objectives of this study were to: (1) determine the number of buildings in Grogol District, Sukoharjo Regency; (2) anlaysis the building density in Grogol District, Sukoharjo Regency. This study uses remote sensing with the Visual Quickbird interpretation method obtained from Google Earth Pro, namely using interpretive elements such as hue / color, shape, texture, and location / association. Visual interpretation is used to determine the number of buildings and building density. The data collection techniques used were image interpretation and field surveys. The data analysis technique used is geographic descriptive, which describes the spatial data analysis. The results of this study were Cemani Village is the village with the highest density of buildings 96.85%, while Parangjoro is the village with the lowest density of buildings with 28.41%.